Fighting performance as a predictor of mating success in male black grouse - Hämäläinen, Anni (2010)
As a consequence of certain conflicting evolutionary interests of males and females, the sexes have taken on different reproductive roles. In many species, where females invest more in the production of offspring, males compete for the opportunities to reproduce and females attempt to choose the highest quality males to sire their offspring. Males of different species signal their quality in a variety of ways, including physical cues such as color signals or exaggerated secondary sexual characters, behavioral signals and acquisition of a dominance status through aggression towards other males. In the lekking black grouse only a few males manage to copulate and active fighting is required for a male to defend a territory which is a prerequisite for mating. Central territories and various physical signals have previously been associated with male mating success and in this study the connection of these factors to male fighting activity was studied. Fights between males were videotaped and examined in detail to determine the specific components of their fighting behavior. The number of fights engaged in, the total number of opponents fought with, fighting intensity and the winning of fights (characterized by the male turning his back to the opponent after a fight) were recorded from the tapes. These characteristics were examined in relation to the male’s mating success as well as physical measures and parasite counts obtained by capturing the males before the lekking season. Males that fought more often, more intensively and with a higher number of males won their fights more often. Each of the fighting characteristics as well as fight winning predicted mating success reliably. Physical traits, on the other hand, were connected to male age but were not found to relate to fighting behaviors nor to correlate with mating success in these data. Territory position had no direct connection to mating success, but central males spent more time fighting or engaged in a higher number of fights. The results of this study imply that active fighting and dominance combined with age-revealing physical traits reliably signal male quality and may be used by females as mate selection criteria.